Miltefosine Rescue Treatment for Visceral Leishmaniasis Relapse Patient - Anup Bastola; Mitesh Shrestha; Bimal Sharma Chalise; Abhdesh Kumar Mishra; Lina Devkota (Case Reports in Infectious Diseases)
We report the first case of miltefosine rescue treatment carried out for visceral leishmaniasis (VL) relapse patient. Despite undergoing treatment regimens of liposomal amphotericin B (LAMB) 5 mg/kg (standard: 10 mg/kg) daily for 3 days during the first episode followed by LAMB 5 mg/kg stat and paromomycin 15 mg/kg IM for 10 days against the second episode, the patient suffered from a third relapse and was eventually treated with miltefosine 50 mg BID directly observed treatment for 28 days. Prior to treatment, the patient had a history of intermittent fever and vague abdominal pain for one week and epistaxis for 4 days. He had massive splenomegaly, tested positive for the rK39 test, and showed LD bodies in bone marrow aspirate. The patient tested negative for malaria and HIV. Upon treatment completion with miltefosine, the patient had clinically improved and showed no LD bodies in bone marrow.